The history of the formation, destruction and restoration of the Architectural and cultural landscape of Baturyn (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2026)
In the article, the historical stages of the origin, destruction and restoration ofobjects of the architectural and cultural landscape of the city of Baturyn, which urban developmentis associated with the activities of five Hetmans of Ukraine – Demian Ihnatovych (1669-1672), IvanSamoilovych (1672-1687), Ivan Mazepa (1687-1708), Pylyp Orlyk (1710-1742) and KyryloRazumovsky (1750-1764) are considered. It is noted that the restoration and reconstruction of thearchitectural and cultural heritage of historical cities of Ukraine is one of the conditions for thepreservation and regeneration of the historical memory of Ukrainians.The history of the urban development of Baturyn associated with the construction of thefortress and its citadel, around which the urban environment of the medieval city was formed, aswell as its decline associated with the attack of the Moscow army, is studied. The period of revivalof the Hetman's capital is described, thanks to the state-building and economic activities of the lastHetman of Ukraine Kyrylo Razumovsky in 1750-1764.The history of the creation of the palace and park complex of K. Razumovsky by CharlesCameron and Antonio Rinaldi, its neglect and revival at the beginning of the 21st centurysimultaneously with other objects of the architectural and cultural landscape of today's Baturyn ispresented, namely: the citadel of the Baturyn fortress (1620); the estate of V.L. Kochubei with apark area located within the ancient Cossack park (late XVII – mid - XIX). K. Razumovsky (1799-1803) with a parish school (1897). Okhor No. 883.The experience of successful implementation of the “Comprehensive Program for thePreservation of Monuments of the State Historical and Cultural Reserve “Hetman's Capital” and theDevelopment of Social and Engineering and Transport Infrastructure of Baturyn Village” at theexpense of public-private partnership in the field of financing restoration and construction works isdescribed.
Keywords: architectural and cultural landscape of the historical city; reconstruction of the Baturyn citadel; restoration of the palace of Kyrylo Razumovsky; architects Charles Cameron; Antonio Rinaldi; Andrii Bilohrud